Denitrogenation of model oil using imidazalium-based ionic liquid - Mohd Hanafi, Shaari (2013)
Removal of aromatic nitrogen contaminants from petroleum is important for many reasons. First, their combustion leads directly to the formation of nitrogen oxides (NOx); emissions of NOx, which contributes to acid rain, are under increasingly stringent control by environmental regulation. This thesis contains the study of Model Oil (iso-octane) by extraction with imidazalium-based ionic liquid. The objective of this experiment is to determine the nitrogen compound (Pyridine) removal efficiency of imidazalium-based ionic liquid (3-ethylimidazalium-ethyl phosphate) from iso-octane. In order to characterize the imidazalium based ionic liquids, the process of characterization of 3-ethylimidazalium-ethyl phosphate was conducted by using Fourier Transform Infra Red (FTIR) spectroscopy.